Alteration of The Properties of Spent Eucalyptus Biomass from Steam Distillation - Yani, Syamsuddin; Yani, Setyawati (Chemical Engineering Department, Engineering Faculty, Universitas Sultan Ageng Tirtayasa, 2021)
Steam distillation is a common method to extract the eucalyptus oil from eucalyptus biomass. The spent biomass of the steam distillation process could be used as biofuel feedstock. This study aims to investigate the effect of eucalyptus biomass steam distillation time on the alteration of the spent biomass. The properties studied include carbon retention, fuel properties namely proximate and ultimate analyses as well as grindability. Those properties were investigated from 5 to 180 minutes of the distillation time. The grindability and fuels chemistry of spent biomass were little affected by the steam distillation process. The results show that to use the spent biomass of steam distillation as a feedstock for bioenergy production it is quite promising.